Colorimetric detection of heat-labile toxin-encoding gene of enterotoxigenic Escherichia coli by PCR. - O'Meara, D (1995)
In the developing world, enterotoxigenic Escherichia coli (ETEC) strains which produce enterotoxins are a significant cause of morbidity and mortality. Heat-labile (LT) toxin PCR detection methods have been described, but they have limited applications in a routine laboratory setting. A colorimetric DNA method for the rapid amplification and detection of the LT toxin gene in ETEC strains is described. Target amplification together with colorimetric detection would overcome many of the limitations of conventional PCR. This paper describes a colorimetric PCR detection method specific for LT-gene-encoding ETEC strains. DNA was extracted from two representative colonies from each bacterial isolate and amplified by PCR. Digoxigenin was incorporated into the amplification product, permitting a one-step direct detection using anti-digoxigenin alkaline phosphatase-conjugated antibody. This technique was applied to the investigation of 70 E. coli isolates derived from clinical fecal samples obtained from an Irish population. Eleven percent of the samples were LT positive, confirming the applicability of this method. All LT-positive ETEC strains (controls and clinical isolates) were detected, and no false-positive results occurred.